1997
DOI: 10.3109/00207459708988471
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Rise in Serum Anti-Brain Autoantibody Levels in the Rat

Abstract: Sera from Wistar rats subjected to different stress procedures were tested by ELISA for the presence of autoantibodies with specificity for neuron-specific enolase (NSE) and S100 protein that are preferentially localized in neurons and glia, respectively. Autoantibodies were present in sera of animals before exposure to stress, and raised with age. Anti-NSE and anti-S100 autoantibody levels were increased one day after termination of restraint (2 hours daily, 10 days) and electric tail shock (80 shocks daily, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…A previous study on the same pigs revealed that temporary regrouping activated the classical complement pathway and increased serum haptoglobin levels, suggesting acute regrouping stress (Reimert et al, 2014a). Moreover, others reported a rise in serum autoantibodies after acute (restraint) stress (Andrejević et al, 1997). Regrouping leads to mutual ranking fights, which can be quite vigorous.…”
Section: Regrouping Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous study on the same pigs revealed that temporary regrouping activated the classical complement pathway and increased serum haptoglobin levels, suggesting acute regrouping stress (Reimert et al, 2014a). Moreover, others reported a rise in serum autoantibodies after acute (restraint) stress (Andrejević et al, 1997). Regrouping leads to mutual ranking fights, which can be quite vigorous.…”
Section: Regrouping Effectsmentioning
confidence: 90%
“…A large part of the NAb repertoire is directed to self-antigens, and these antibodies are referred to as NAAb. Blood levels of autoantibodies-binding neural antigens have been related to acute and chronic stress (Andrejević et al, 1997;Zhou et al, 1999), and could both reflect and affect neuronal functioning (Gold et al, 2012). Myelin basic protein (MBP) is an important protein in the process of myelination of nerves in the nervous system, and it has been found that high levels of autoantibodies to MBP and other neural antigens were associated with neurological damage (Abou-Donia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effects of overcrowding on the parameters of immune system in rodents. IL-1β takes part in stimulation of the hypothalamic-pituitary-adrenal axis in rats exposed to chronic overcrowding (24 specimens per cage) [14], and the level of antibodies against brain tissue increases in blood serum of these animals [9]. The effects of chronic overcrowding on rat immunity have not been studied yet.…”
mentioning
confidence: 99%
“…A previous study on the same pigs revealed that temporary regrouping activated the classical complement pathway and increased serum haptoglobin levels, suggesting acute regrouping stress (Reimert et al 2014b). Also others reported a rise in serum auto-antibodies after acute (restraint) stress (Andrejević et al 1997).…”
Section: Regrouping Effectsmentioning
confidence: 85%
“…repertoire is directed to self-antigens, and these antibodies are referred to as natural auto-antibodies (NAAb). Blood levels of auto-antibodies binding neural antigens have been related to acute and chronic stress (Andrejević et al 1997;Zhou et al 1999), and could both reflect and affect neuronal functioning (Gold et al 2012). Myelin basic protein (MBP) is an important protein in the process of myelination of nerves in the nervous system.…”
Section: Introductionmentioning
confidence: 99%